Breakfast frequency, adiposity, and cardiovascular risk factors as markers in adolescents - Cayres, Suziane U. [UNESP]; Júnior, Ismael F. F. [UNESP]; Barbosa, Maurício F.; Christofaro, Diego G. D. [UNESP]; Fernandes, Rômulo A. [UNESP] (Cambridge University Press, 2015)
To analyse the relationship between skipping breakfast and haemodynamic, metabolic, inflammatory, and cardiovascular risk factors in adolescents. A cross-sectional study was carried out with information from an ongoing cohort study in Presidente Prudente, São Paulo, Brazil. The sample comprised of 120 adolescents (11.7±0.8 years old) who met the following inclusion criteria: age between 11 and 14 years; enrolled in the school unit of elementary education; absence of any known disease; and no drug consumption. The parents or legal guardians of the patients signed a formal informed consent. Skipping breakfast was self-reported through face-to-face interviews. Blood pressure, intima-media thickness, trunk fatness, total and fractional cholesterol levels - high-density lipoprotein cholesterol and low-density lipoprotein cholesterol - triacylglycerol levels, and high-sensitivity C-reactive protein levels were measured. In this study, 47.5% (95% CI: 38.5-56.4%) of the adolescents reported skipping breakfast at least 1 day/week. Adolescents who skipped breakfast had higher values of trunk fatness and systolic blood pressure. Breakfast frequency was negatively related to systolic blood pressure (β -1.99 [-3.67; -0.31]) and z score dyslipidaemia (β -0.46 [-0.90; -0.01]), but this relationship was mediated by trunk fatness. Skipping breakfast is related to cardiovascular risk factors in adolescents, and this relationship was mainly mediated by trunk fatness.
Keywords: Adolescent; Cardiovascular risk factors; Skipping breakfast